Experimental research on the technology of manufacturing and burning of aircraft structures made of multicomponent materials - V. I. Trushlyakov; D. Ya. Davydovich (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The analysis of the state of modern technologies for utilization of reinforced polymers is carried out. The task of the study was formulated. Based on thermodynamic analysis and consideration of various combinations of compositions for conducting experiments, six types of test multicomponent samples were selected for conducting experimental studies on their combustion. To determine the maximum combustion temperature, the ignition temperature of the samples, and the mass of combustion residues. The analysis of the results obtained was carried out, and the compositions of the components for further research were identified